Recycled cement concrete road and construction method thereof
By designing and constructing recycled cement concrete roads, solid waste and waterway clay generated by canal excavation, bridge demolition and abandoned building concrete, the problems of solid waste treatment and traditional cement concrete roads are solved, and the recycling of resources and the improvement of road performance are achieved.
Patent Information
- Application Number
- CN202510003369.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, solid waste generated by canal excavation, bridge demolition and abandoned building concrete cannot be effectively utilized, resulting in environmental pollution and waste of resources. At the same time, traditional cement concrete roads have problems such as high maintenance costs, poor wear resistance, and large resource consumption.
A method of design and construction of recycled cement concrete roads is adopted to recycle solid waste and waterway clay from canal excavation, bridge removal and waste building concrete to form a multi-layer structure road, including a curing-free anti-slip wear layer, a high-strength cementitious bonding layer, a curing-free recycled cement stable gravel base layer, a permeable cementitious bonding layer and a recycled soil base layer.
The recycling of renewable resources is realized, the cost of solid waste treatment and construction is reduced, the wear resistance, durability and strength of the road is improved, the service life of the road is extended, and subsequent maintenance costs are reduced.
Smart Images

Figure CN119800792A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to road engineering, in particular to a recycled cement concrete road and a construction method thereof. Background Art
[0002] At present, solid waste generated by canal excavation, bridge demolition and abandoned building concrete is usually disposed of by open-air stacking or simple landfill, which causes dust and harmful substances to pollute the atmosphere, water and soil environment. The stacked solid waste also incurs additional site rental fees, labor costs, etc., and the recyclable resources in the solid waste cannot be reasonably utilized. The canal waterway bears the high load and wear caused by heavy-loaded vehicles and ship loading and unloading operations while assuming the function of vehicle passage. The existing canal waterway auxiliary roads are mostly made of traditional cement concrete materials, which have problems such as high maintenance cost, poor wear resistance, and high resource consumption.
[0003] The patent with publication number CN105669100A discloses a road cushion concrete recycled from construction waste and its preparation method, which recycles construction waste and adds bamboo fiber for modification. However, there is no prior art that uses solid waste generated by canal excavation, bridge demolition and abandoned construction concrete and waterway clay in road construction. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a recycled cement concrete road that fully utilizes solid waste generated by canal excavation, bridge demolition and abandoned building concrete; another purpose of the present invention is to provide a construction method for recycled cement concrete roads.
[0005] Technical solution: The recycled cement concrete road described in the present invention comprises, from top to bottom, a maintenance-free anti-skid wear layer, a high-strength cementitious material bonding layer, a maintenance-free recycled cement stabilized crushed stone base, a permeable cementitious material bonding layer and a recycled soil base; the maintenance-free anti-skid wear layer comprises the following materials in parts by weight: 5-10 parts of maintenance-free materials, 15-25 parts of wear-resistant aggregates, 3-6 parts of epoxy resins and 4-8 parts of water; the maintenance-free materials comprise 10-20 parts of silty clay, 3-6 parts of nano diatomaceous earth and 3-6 parts of outer shell protective layer; the outer shell protective layer comprises 10-15 parts of porous recycled concrete and 2-4 parts of polypropylene fibers; the porous recycled concrete comprises 10-20 parts of a recycled coarse and fine aggregate mixture, 3-6 parts of water and 2-4 parts of alkali slag cementitious materials; The high-strength cementitious bonding layer includes the following materials in mass parts: 5-9 parts of high-strength cement clinker, 2-5 parts of slag powder, 2-5 parts of microsilica powder and 1-3 parts of water; the maintenance-free recycled cement stabilized gravel base layer includes the following materials in mass parts: 15-20 parts of recycled graded gravel, 3-6 parts of water-absorbing resin, 3-6 parts of cement and 5-8 parts of water; the permeable cementitious material bonding layer includes the following materials in mass parts: 2-4 parts of magnesium silicate, 2-4 parts of sodium silicate, 5-10 parts of fine recycled powder and 2-4 parts of water; the recycled soil base layer includes the following materials in mass parts: 30-40 parts of canal abandoned soil and slag, 5-10 parts of recycled building fine aggregate and 3-6 parts of adhesive; the adhesive includes 3-5 parts of cement, 5-10 parts of fly ash, 5-10 parts of slag and 2-4 parts of water. The outer shell protective layer forms an isolation layer on the surface of the material to prevent water evaporation, accelerate the hydration reaction of active oxides in the material, reduce the voids inside the material, form a dense structure with filling and bonding functions, and improve the overall strength, thereby achieving a maintenance-free effect.
[0006] Furthermore, the wear-resistant aggregate includes ceramsite and carbonized wear-resistant recycled coarse aggregate; the ceramsite is obtained by drying, grinding, shaping and screening, preheating and roasting, and cooling and screening the clay soil collected from the canal waste soil; the ceramsite is a continuous particle size distribution of 5 to 30 mm, and its apparent density is not less than 1g / cm 3 , porosity not less than 50%, compressive strength not less than 4.5MPa, polishing value index not less than 50%; the carbonized wear-resistant recycled coarse aggregate is obtained by carbon strengthening the canal abandoned soil at a high temperature of 1000℃-1100℃ for 30-50min, and the crushing index is not more than 13%; the recycled coarse and fine aggregate mixture is obtained by crushing, screening, gradation design, mixing and curing the construction solid waste removed along the canal, and the recycled coarse and fine aggregate mixture is a continuous gradation of 9.5-26.5mm; the alkali slag cementitious material is obtained by reacting slag with alkali solution; the water absorption rate of the silty clay is not less than 35%; the specific surface area of the nano diatomaceous earth is not less than 550m 2 / g, and a porosity of not less than 85%; the porosity of the outer shell protective layer is not less than 35%, and a water permeability coefficient is not less than 1cm / s.
[0007] Furthermore, the recycled graded gravel is obtained by crushing, screening, shaping, cleaning and removing impurities from construction solid waste dismantled along the canal. The recycled graded gravel has a continuous particle size gradation of 5 to 20 mm, and the ratio of each particle size range is 5 to 10 mm: 10 to 15 mm: 15 to 20 mm = 1:1:2. The compaction degree is not less than 97%, and the crushing index is not more than 20%.
[0008] Furthermore, the fine recycled powder is obtained by ball milling, shaping and chemical activation of waste concrete blocks from canal excavation, demolished bridges and house buildings, including CaO, SiO2 and Al2O3. The MB value of the fine recycled powder is not more than 1.35, and the specific surface area is not less than 450m 2 / kg.
[0009] Furthermore, the abandoned soil and slag from the canal has a moisture content of no more than 11% after refinement and dehydration; the recycled construction fine aggregate is processed from construction solid waste removed along the canal, has a particle size of no more than 4.75 mm, and no less than 10% of the particles pass through a 0.075 mm sieve.
[0010] Furthermore, the mineral composition of the high-strength cement clinker has an active mass component of not less than 90%, of which the content of tricalcium silicate is not less than 69%; the purity of the microsilica powder is greater than 86%, and the specific surface area is 16 to 25 m 2 / g.
[0011] Furthermore, the water-absorbing resin is a sodium polyacrylate resin or a cellulose-based water-absorbing resin.
[0012] Furthermore, the penetration depth of the penetrating gelling material bonding layer is 1-3 cm.
[0013] Furthermore, the interlayer bonding strength of the high-strength gelling bonding layer is not less than 0.8 MPa, and the compressive strength is not less than 20 MPa.
[0014] The construction method of the recycled cement concrete road of the present invention comprises the following steps:
[0015] (1) Spoil and slag from the canal, recycled building fine aggregate and adhesive are mixed to obtain a mixture, which is laid on the base with a flatness of no more than 8 mm and a thickness of 15 cm to 20 cm, and then compacted to obtain a recycled soil base;
[0016] (2) Magnesium silicate, sodium silicate, fine regeneration powder and water are uniformly stirred in a stirring device until a homogeneous bonding cementitious material is formed, and then the material is evenly spread on the regenerated soil base to form a permeable cementitious material bonding layer;
[0017] (3) uniformly mixing the recycled graded crushed stone, water-absorbing resin, cement and water to form a maintenance-free recycled cement-stabilized crushed stone material, spreading, leveling and compacting the material on the permeable cementitious material bonding layer, with a compaction degree of not less than 97%, to obtain a maintenance-free recycled cement-stabilized crushed stone base layer;
[0018] (4) Put high-strength cement clinker, slag powder, microsilica powder and water into a mixing equipment and mix them evenly until a homogeneous bonding cementitious material is formed. Spread the prepared cementitious material on the maintenance-free recycled cement stabilized gravel base with a spreading amount of 0.5-1kg / m 2 , obtaining a high-strength cementitious material bonding layer;
[0019] (5) First, a mixture of recycled coarse and fine aggregates, water and alkali slag cementitious materials are mixed to obtain porous recycled concrete, and then the porous recycled concrete and polypropylene fiber are mixed to obtain a shell protective layer, and then silty clay, nano diatomaceous earth and the shell protective layer are mixed, and mixed evenly using a mixing device to obtain a maintenance-free material; finally, the maintenance-free material, wear-resistant aggregate, epoxy resin and water are mixed, and then evenly spread on a maintenance-free recycled cement stabilized gravel base for rolling to obtain a maintenance-free anti-skid wear layer, and the construction of the recycled cement concrete road is completed.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0021] 1. Realize the recycling of renewable resources, effectively solve the problem of large-scale solid waste treatment, and significantly reduce the cost of concrete road construction and solid waste treatment;
[0022] 2. The road has better wear resistance, durability and strength, and has good crack resistance, which effectively reduces the occurrence of cracks, extends the service life of the road, and reduces subsequent maintenance costs;
[0023] 3. The road construction is simple and can shorten the construction period. The on-site cold recycling technology can effectively avoid the dust problem during the transportation of materials, which is beneficial to the protection of the ecological environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a structural schematic diagram of the present invention. DETAILED DESCRIPTION
[0025] In the following examples, the materials and reagents used are all commercially available unless otherwise specified. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0026] Example 1
[0027] The maintenance-free anti-skid wear layer of the recycled cement concrete road includes the following materials in proportion by mass: 5 parts of maintenance-free materials, 15 parts of wear-resistant aggregates, 3 parts of epoxy resins and 4 parts of water, wherein the maintenance-free materials include 10 parts of silty clay, 3 parts of nano-diatomaceous earth and 3 parts of outer shell protective layer, wherein the outer shell protective layer includes 10 parts of porous recycled concrete and 2 parts of polypropylene fibers, and the porous recycled concrete includes 10 parts of a mixture of recycled coarse and fine aggregates, 3 parts of canal water and 2 parts of alkali slag cementitious materials.
[0028] The wear-resistant aggregate includes ceramsite and carbonized wear-resistant recycled coarse aggregate. The ceramsite is obtained by drying, grinding, shaping, screening, preheating and roasting, and finally cooling and screening. The particle size classification is mainly divided into 5-10 mm, accounting for 62% of the mass fraction, 10-20 mm, accounting for 28% of the mass fraction, and 20-30 mm, accounting for 10% of the mass fraction. The apparent density of the ceramsite is 1g / cm 3 , porosity is 50%, compressive strength is 4.5MPa, and polishing value index is 50%. Carbonized wear-resistant recycled coarse aggregate is obtained by carbonizing canal waste soil at a high temperature of 1000℃ for 30min. Carbon strengthening improves the strength of aggregate. CO2 reacts with carbonizable substances such as calcium hydroxide and hydrated calcium silicate in the recycled aggregate to generate carbonized materials such as SiC and CaCO3, which are mainly composed of calcium carbonate and silica gel. The crushing index of carbonized wear-resistant recycled aggregate is 13%. The recycled coarse and fine aggregate mixture is obtained by crushing and screening, particle size grading design, mixing and curing. The recycled coarse and fine aggregate mixture has a particle size classification of 4 levels, among which the particle size of 9.5-13.2mm is 11.5wt%, 13.2-16mm is 15.5wt%, 16-19mm is 16wt%, and 19-26.5mm is 57wt%. Alkali slag cementitious material, made by the reaction of slag and alkaline solution. The porosity of the outer shell protective layer is 35%, and the water permeability coefficient is 1cm / s; the water absorption rate of silty clay is 35%; the specific surface area of nano diatomite is 550m 2 / g, and the porosity is 85%.
[0029] The interlayer bonding strength of the high-strength cementitious material bonding layer is 0.8MPa, and the compressive strength is 20Mpa. It includes the following materials by mass: 5 parts of high-strength cement clinker, 2 parts of slag powder, 2 parts of microsilica powder and 1 part of water; the mineral composition of the high-strength cement clinker has an active mass component of 90%, and the content of tricalcium silicate is 69%; the purity of the microsilica powder is 86%, and the specific surface area is 16m 2 / g.
[0030] The maintenance-free recycled cement-stabilized crushed stone base layer includes the following materials by weight: 15 parts of recycled graded crushed stone, 3 parts of water-absorbing resin, 3 parts of cement and 5 parts of water. The recycled graded crushed stone is obtained by crushing, screening, shaping and cleaning and removing impurities from bridges and buildings demolished along the canal. Its particle size classification is 3 levels: 5-10mm accounts for 25% of the mass ratio, 10-15mm accounts for 25% of the mass ratio, 15-20mm accounts for 50% of the mass ratio, the compaction degree is 97%, and the crushing index is 20%. The water-absorbing resin is a sodium polyacrylate resin.
[0031] The penetration depth of the bonding layer of the penetrating cementitious material is 1 cm, and it includes the following materials by mass: 2 parts of magnesium silicate, 2 parts of sodium silicate, 5 parts of fine recycled powder and 2 parts of water; the fine recycled powder is obtained by ball milling, shaping and chemical activation of abandoned concrete blocks from canal excavation, demolished bridges and house buildings, including CaO, SiO2 and Al2O3, and its particle grading and particle size are 3 levels, 0.045mm particles account for 35.42%, 0.075mm particles account for 53.58%, 0.01mm particles account for 22.1%, the MB value of methylene blue is 1.35, and the specific surface area is 450m 2 / kg.
[0032] The regenerated soil base layer includes the following materials in proportion by mass: 30 parts of canal abandoned soil and slag, 5 parts of recycled building fine aggregate and 3 parts of adhesive, the adhesive includes 3 parts of cement, 5 parts of fly ash, 5 parts of slag and 2 parts of water; the canal abandoned soil and slag has a moisture content of 11% after refinement and dehydration; the main components of the recycled building fine aggregate are particles with a particle size not greater than 4.75mm made from concrete, mortar, stone or bricks and tiles removed from bridges and houses on the canal, 10% of which pass through a sieve of 0.075mm, and the dosage is 25% of the mass of the abandoned soil and slag used for the regenerated soil base layer.
[0033] The construction method of the above-mentioned recycled cement concrete road comprises the following steps:
[0034] (1) A mixture of canal waste soil and slag, recycled building fine aggregate and adhesive in a ratio of 6:1:0.6 is obtained, and the mixture is laid on the base with a grader to a flatness of 8 mm and a thickness of 15 cm, and then compacted with a roller to obtain a recycled soil base;
[0035] (2) Magnesium silicate, sodium silicate, fine regeneration powder and water are put into a stirring pot in a ratio of 1:1:2.5:1 and stirred evenly for 15 minutes at a stirring rate of 40 r / min until a homogeneous bonding cementitious material is formed, and then evenly laid on the regenerated soil base, and the penetration depth of the permeable cementitious material bonding layer is 1 cm;
[0036] (3) mixing recycled graded crushed stone, water-absorbing resin, cement and water in a ratio of 3:0.6:0.6:1 to form a maintenance-free material, spreading, leveling and compacting the maintenance-free material to a compaction degree of 97%, thereby obtaining a maintenance-free recycled cement-stabilized crushed stone base;
[0037] (4) First, high-strength cement clinker, slag powder, microsilica powder and water were put into a mixing pot in a ratio of 5:2:2:1 and stirred evenly for 10 minutes at a stirring rate of 50 r / min until a homogeneous bonding cementitious material was formed with an interlayer bonding strength of 0.8 MPa and a compressive strength of 20 MPa. The prepared cementitious material was spread on the maintenance-free recycled cement stabilized gravel base with a spreading amount of 0.5 kg / m 2 , obtaining a high-strength cementitious material bonding layer;
[0038] (5) First, the recycled coarse and fine aggregate mixture, canal water and alkali slag cementitious material are mixed in a ratio of 5:1.5:1 to obtain porous recycled concrete material, and then the porous recycled concrete and polypropylene fiber are mixed in a ratio of 5:1 to obtain the outer shell protective layer material, and then the silty clay, nano diatomaceous earth and outer shell protective layer are mixed in a ratio of 1:0.3:0.3, and stirred evenly in a stirring pot for 10 minutes at a stirring rate of 40r / min to obtain maintenance-free material, 5 parts of maintenance-free material, 15 parts of wear-resistant aggregate, 3 parts of epoxy resin and 4 parts of water are mixed, and spread and rolled on the high-strength cementitious material bonding layer, and the construction of the recycled cement concrete road is completed.
[0039] Example 2
[0040] The maintenance-free anti-skid wear layer of the recycled cement concrete road includes the following materials in mass proportions: 7 parts of maintenance-free materials, 20 parts of wear-resistant aggregates, 4 parts of epoxy resins and 6 parts of water; the maintenance-free materials include 15 parts of silty clay, 4 parts of nano-diatomaceous earth and 4 parts of shell protective layer; the shell protective layer includes 12 parts of porous recycled concrete and 3 parts of polypropylene fiber; the porous recycled concrete includes 15 parts of recycled coarse and fine aggregate mixture, 4 parts of canal water and 3 parts of alkali slag cementitious materials. The wear-resistant aggregate is composed of ceramsite and carbonized wear-resistant recycled coarse aggregate. The ceramsite is obtained by drying, grinding, shaping, screening, preheating and roasting, and finally cooling and screening. The particle size classification is mainly divided into 5-10mm, accounting for 60.5% of the mass proportion, 10-20mm, accounting for 27.2% of the mass proportion, and 20-30mm, accounting for 9.4% of the mass proportion. The apparent density of ceramsite is 1.2g / cm 3, porosity is 52%, compressive strength is 4.65MPa, and polishing value index is 52%. Carbonized wear-resistant recycled coarse aggregate is obtained by carbon strengthening canal abandoned soil at a high temperature of 1050℃ for 40 minutes. Its particle size classification is 4 levels, among which 9.5-13.2mm aggregate accounts for 11% by mass, 13.2-16mm aggregate accounts for 15% by mass, 16-19mm aggregate accounts for 14.5% by mass, 19-26.5mm aggregate accounts for 55.6% by mass, and the crushing index is 11.5%. Alkali slag cementitious material is obtained by reacting slag with alkaline solution. The water absorption rate of silty clay is 37%; the specific surface area of nano diatomaceous earth is 570m 2 / g, the porosity is 86.5%; the porosity of the outer shell protective layer is 36.5%, and the water permeability coefficient is 1.5cm / s.
[0041] The interlayer bonding strength of the high-strength cementitious material bonding layer is 0.85MPa, and the compressive strength is 22Mpa. It includes the following materials by mass: 6 parts of high-strength cement clinker, 3 parts of slag powder, 3 parts of microsilica powder and 2 parts of water. The mineral composition of high-strength cement clinker has an active mass component of 92%, and a tricalcium silicate content of 70%; microsilica powder has a purity of 88% and a specific surface area of 16 to 25m 2 / g.
[0042] The maintenance-free recycled cement-stabilized gravel base layer includes the following materials in proportion by mass: 17 parts of recycled graded gravel, 4 parts of water-absorbent resin, 4 parts of cement and 6 parts of water; the recycled graded gravel is obtained by crushing, screening, shaping, cleaning and removing impurities from bridges and building structures dismantled along the canal, and its particle size classification is 3 levels: 5-10 mm accounts for 24.1% of the mass proportion, 10-15 mm accounts for 24.5% of the mass proportion, and 15-20 mm accounts for 48.3% of the mass proportion. The compaction degree of the recycled graded gravel is 98%, and the crushing index is 18.5%; the water-absorbent resin is a mixture of sodium polyacrylate resin and cellulose-based water-absorbent resin in a ratio of 1:1.
[0043] The penetration depth of the bonding layer of the penetrating cementitious material is 2 cm, and it includes the following materials by mass: 3 parts of magnesium silicate, 3 parts of sodium silicate, 7 parts of fine recycled powder and 3 parts of water; the fine recycled powder is obtained by ball milling, shaping and chemical activation of abandoned concrete blocks from canal excavation, demolished bridges and house buildings, including CaO, SiO2 and Al2O3, with a particle size distribution of 0.045 mm particles accounting for 34.7%, 0.075 mm particles accounting for 52.5%, and 0.01 mm particles accounting for 21.9%. The MB value of methylene blue is 1.30, and the specific surface area is 485m 2 / kg.
[0044] The regenerated soil base includes the following materials by mass: 35 parts of canal abandoned soil and slag, 7 parts of recycled building fine aggregate and 4 parts of adhesive; the adhesive includes the following materials by mass: 4 parts of cement, 7 parts of fly ash, 7 parts of slag and 3 parts of water. The canal abandoned soil and slag has a moisture content of 10% after refinement and dehydration. The main components of the recycled building fine aggregate are particles with a particle size of no more than 4.75mm processed from concrete, mortar, stone or bricks and tiles from the demolished bridges and houses of the canal, and the particles passing through the 0.075mm sieve account for 12%. The admixture is 30% of the mass of the abandoned soil and slag used in the regenerated soil base.
[0045] The construction method of the above-mentioned recycled cement concrete road comprises the following steps:
[0046] (1) A mixture is obtained by mixing the canal waste soil and slag, recycled building fine aggregate and adhesive in a ratio of 8.75:1.75:1, and laying it on the base with a grader to a flatness of 6 mm and a thickness of 17 cm, and then compacting it with a roller to obtain a recycled soil base;
[0047] (2) Magnesium silicate, sodium silicate, fine regeneration powder and water are put into a stirring pot in a ratio of 3:3:7:3 and stirred evenly for 20 minutes at a stirring rate of 50 r / min until a homogeneous bonding cementitious material is formed, and then evenly laid on the regenerated soil base to form a permeable cementitious material bonding layer with a penetration depth of 2 cm;
[0048] (3) Mixing recycled graded crushed stone, water-absorbing resin, cement and water in a ratio of 4.25:1:1:1.5 to form a maintenance-free material, and spreading, leveling and compacting the maintenance-free material on the permeable cementitious material bonding layer to a compaction degree of 97.5%;
[0049] (4) First, high-strength cement clinker, slag powder, microsilica powder and water were put into a mixing pot in a ratio of 3:1.5:1.5:1 and stirred evenly for 15 minutes at a stirring rate of 65 r / min until a homogeneous bonding cementitious material was formed with an interlayer bonding strength of 0.85 MPa and a compressive strength of 22 MPa. The prepared cementitious material was spread on the maintenance-free recycled cement stabilized gravel base with a spreading amount of 0.5 kg / m 2 ;
[0050] (5) First, the recycled coarse and fine aggregate mixture, canal water and alkali slag cementitious material are mixed in a ratio of 3.75:1:0.75 to obtain porous recycled concrete, and then the porous recycled concrete and polypropylene fiber are mixed in a ratio of 4:1 to form an outer shell protective layer. Then, silty clay, nano diatomaceous earth and the outer shell protective layer are mixed in a ratio of 3.75:1:1, and stirred evenly in a stirring pot for 15 minutes at a stirring rate of 50r / min to obtain maintenance-free material. 7 parts of maintenance-free material, 20 parts of wear-resistant aggregate, 4 parts of epoxy resin and 6 parts of water are mixed, and spread and rolled on the high-strength cementitious material bonding layer, and the construction of the recycled cement concrete road is completed.
[0051] Example 3
[0052] The maintenance-free anti-skid wear layer of the recycled cement concrete road includes the following materials in mass proportions: 10 parts of maintenance-free materials, 25 parts of wear-resistant aggregates, 6 parts of epoxy resins and 8 parts of water; the maintenance-free materials include 20 parts of silty clay, 6 parts of nano-diatomaceous earth and 6 parts of shell protective layer; the shell protective layer includes 15 parts of porous recycled concrete and 4 parts of polypropylene fiber; the porous recycled concrete includes 20 parts of recycled coarse and fine aggregate mixture, 6 parts of canal water and 4 parts of alkali slag cementitious materials. The wear-resistant aggregate is composed of ceramsite and carbonized wear-resistant recycled coarse aggregate. The ceramsite is obtained by drying, grinding, shaping, screening, preheating and roasting, and finally cooling and screening. Its particle size classification is mainly divided into 5-10mm accounting for 60% of the mass proportion, 10-20mm accounting for 26.9% of the mass proportion, 20-30mm accounting for 9% of the mass proportion, and the apparent density of ceramsite is 1.5g / cm 3 , porosity is 53%, compressive strength is 4.8MPa, polishing value index is 53.5%. Carbonized wear-resistant recycled coarse aggregate is obtained by carbon strengthening canal abandoned soil at a high temperature of 1100℃ for 50min. Its particle size classification is 4 levels, 9.5-13.2mm aggregate accounts for 10.5% by mass, 13.2-16mm aggregate accounts for 14.5% by mass, 16-19mm aggregate accounts for 14.5% by mass, 19-26.5mm aggregate accounts for 55.2% by mass, and the crushing index is 11%. Alkali slag cementitious material, obtained by reacting slag with alkaline solution. The porosity of the outer shell protective layer is 37%, and the water permeability coefficient is 2cm / s; the water absorption rate of silty clay is 38.5%; the specific surface area of nano diatomaceous earth is 585m 2 / g, and the porosity is 88%.
[0053] The interlayer bonding strength of the high-strength cementitious material bonding layer is 0.88MPa, and the compressive strength is 23Mpa. It includes the following materials by mass: 9 parts of high-strength cement clinker, 5 parts of slag powder, 5 parts of microsilica powder and 3 parts of water; the mineral composition of the high-strength cement clinker has an active mass component of 93%, and the content of tricalcium silicate is 71%; the purity of the microsilica powder is 89%, and the specific surface area is 25m 2 / g.
[0054] The maintenance-free recycled cement-stabilized gravel base layer includes the following materials in proportion by mass: 20 parts of recycled graded gravel, 6 parts of water-absorbent resin, 6 parts of cement and 8 parts of water; the recycled graded gravel is obtained by crushing, screening, shaping, cleaning and removing impurities from bridges and building structures dismantled along the canal, and its particle size classification is divided into 3 grades: 5-10 mm accounts for 23.7% of the mass proportion, 10-15 mm accounts for 23.5% of the mass proportion, 15-20 mm accounts for 47.9% of the mass proportion, the compaction degree is 98.5%, and the crushing index is 18%; the water-absorbent resin is a cellulose-based water-absorbent resin.
[0055] The penetration depth of the bonding layer of the penetrating cementitious material is 3 cm, and it includes the following materials by mass: 4 parts of magnesium silicate, 4 parts of sodium silicate, 10 parts of fine recycled powder and 4 parts of water; the fine recycled powder is obtained by ball milling, shaping and chemical activation of abandoned concrete blocks from canal excavation, demolished bridges and house buildings, including CaO, SiO2 and Al2O3, with a particle grading and particle size of 3 levels, 0.045 mm particles account for 34.4%, 0.075 mm particles account for 52.1%, 0.01 mm particles account for 21.2%, the MB value of methylene blue is 1.27, and the specific surface area is 495m 2 / kg.
[0056] The regenerated soil base layer includes the following materials in proportion by mass: 40 parts of canal abandoned soil and slag, 10 parts of recycled building fine aggregate and 6 parts of adhesive; the adhesive includes the following materials in proportion by mass: 5 parts of cement, 10 parts of fly ash, 10 parts of slag and 4 parts of water; the canal abandoned soil and slag has a moisture content of 9.7% after refinement and dehydration; the main components of the recycled building fine aggregate are particles with a particle size not greater than 4.75 mm processed from concrete, mortar, stone or bricks and tiles from the demolished bridges and houses on the canal, and 12.5% of the particles pass through a sieve of 0.075 mm. The dosage of the recycled building fine aggregate is 35% of the mass of the abandoned soil and slag used in the regenerated soil base layer.
[0057] The construction method of the above-mentioned recycled cement concrete road comprises the following steps:
[0058] (1) A mixture of canal waste soil and slag, recycled building fine aggregate and adhesive in a ratio of 4:1:0.6 is obtained, and the mixture is laid on the base with a grader to a flatness of 5 mm and a thickness of 20 cm, and then compacted with a roller to obtain a recycled soil base;
[0059] (2) Magnesium silicate, sodium silicate, fine regeneration powder and water are put into a stirring pot in a ratio of 0.4:0.4:1:0.4 and stirred evenly for 25 minutes at a stirring rate of 60 r / min until a homogeneous bonding cementitious material is formed, and then evenly laid on the regeneration soil base with a penetration depth of 3 cm;
[0060] (3) mixing recycled graded crushed stone, water-absorbing resin, cement and water in a ratio of 1:0.3:0.3:0.4 to form a maintenance-free material, spreading, leveling and compacting the maintenance-free material to obtain a maintenance-free recycled cement-stabilized crushed stone base, and the compaction degree is 98%;
[0061] (4) First, high-strength cement clinker, slag powder, microsilica powder and water were put into a mixing pot in a ratio of 1.8:1:1:0.6 and stirred evenly for 20 minutes at a stirring rate of 80 r / min until a homogeneous bonding cementitious material was formed. The interlayer bonding strength was 0.88 MPa and the compressive strength was 23 MPa. The prepared cementitious material was spread on the maintenance-free recycled cement stabilized gravel base with a spreading amount of 0.5 kg / m 2 ;
[0062] (5) First, the recycled coarse and fine aggregate mixture, canal water and alkali slag cementitious material are mixed in a ratio of 1:0.3:0.2 to obtain porous recycled concrete, and then the porous recycled concrete and polypropylene fiber are mixed in a ratio of 3.75:1 to obtain a shell protective layer, and then the silty clay, nano diatomaceous earth and the shell protective layer are mixed in a ratio of 1:0.3:0.3, and stirred evenly in a stirring pot for 20 minutes at a stirring rate of 60r / min to obtain maintenance-free material, 10 parts of maintenance-free material, 25 parts of wear-resistant aggregate, 6 parts of epoxy resin and 8 parts of water are mixed, and spread and rolled on the high-strength cementitious material bonding layer, and the construction of the recycled cement concrete road is completed.
[0063] The performance test results of the products obtained in Examples 1-3 of the present invention are as follows:
[0064] Table 1 Test results of tensile and compressive strength of maintenance-free anti-sliding wear layer compared with C25
[0065] Test items Example 1 Example 2 Example 3 C25 Tensile strength / Mpa 1.44 1.51 1.47 1.27 Compressive strength / Mpa 14.5 15.8 15.1 11.9
[0066] Table 2 Comparison of tensile and compressive strength of maintenance-free anti-sliding wear layer with C30 test results
[0067] Test items Example 1 Example 2 Example 3 C30 Tensile strength / Mpa 1.44 1.51 1.47 1.43 Compressive strength / Mpa 14.5 15.8 15.1 14.3
[0068] Table 3 Test results of maintenance-free anti-sliding wear layer performance
[0069] Test items Example 1 Example 2 Example 3 Friction coefficient / mm 0.63 0.68 0.74 Construction depth / mm 0.72 0.79 0.85
[0070] Table 4 Test results of bond strength between maintenance-free anti-skid wear layer and maintenance-free recycled cement stabilized crushed stone base
[0071] Test items Example 1 Example 2 Example 3 Bond strength / Mpa 0.59 0.64 0.71
[0072] Table 5 Test results of curing-free recycled cement stabilized gravel base performance
[0073] Test items Example 1 Example 2 Example 3 Compaction degree / % 96 96.4 97.2 28d flexural tensile strength / Mpa 5.1 5.9 6.3
[0074] Table 6 Test results of interlayer bond strength between maintenance-free recycled cement stabilized gravel base and recycled soil base
[0075] Test items Example 1 Example 2 Example 3 Bond strength / Mpa 0.35 0.38 0.44
[0076] Table 7 Test results of overall structure deflection value
[0077] Test items Example 1 Example 2 Example 3 Deflection value / mm 13.4 12.8 11.9
[0078] The research results show that all indicators of the recycled cement concrete road described in the present invention can meet the technical requirements and meet the functional requirements for use as a road.
Claims
1. A recycled cement concrete road, characterized in that: The road comprises, from top to bottom, a maintenance-free anti-skid wear layer, a high-strength cementitious material bonding layer, a maintenance-free recycled cement stabilized crushed stone base layer, a permeable cementitious material bonding layer and a recycled soil base layer; The maintenance-free anti-skid wear layer comprises the following materials in parts by mass: 5-10 parts of maintenance-free materials, 15-25 parts of wear-resistant aggregates, 3-6 parts of epoxy resins and 4-8 parts of water; the maintenance-free materials comprise 10-20 parts of silty clay, 3-6 parts of nano-diatomaceous earth and 3-6 parts of outer shell protective layer; the outer shell protective layer comprises 10-15 parts of porous recycled concrete and 2-4 parts of polypropylene fibers; the porous recycled concrete comprises 10-20 parts of recycled coarse and fine aggregate mixture, 3-6 parts of water and 2-4 parts of alkali slag cementitious material; The high-strength gelling bonding layer comprises the following materials in parts by weight: 5-9 parts of high-strength cement clinker, 2-5 parts of slag powder, 2-5 parts of microsilica powder and 1-3 parts of water; The maintenance-free recycled cement-stabilized crushed stone base comprises the following materials in parts by mass: 15-20 parts of recycled graded crushed stone, 3-6 parts of water-absorbing resin, 3-6 parts of cement and 5-8 parts of water; The permeable gelling material bonding layer comprises the following materials in parts by mass: 2-4 parts of magnesium silicate, 2-4 parts of sodium silicate, 5-10 parts of fine regenerated powder and 2-4 parts of water; The regenerated soil base layer comprises the following materials in parts by mass: 30-40 parts of canal abandoned soil and slag, 5-10 parts of recycled building fine aggregate and 3-6 parts of adhesive; the adhesive comprises 3-5 parts of cement, 5-10 parts of fly ash, 5-10 parts of slag and 2-4 parts of water.
2. The recycled cement concrete road according to claim 1, characterized in that: The wear-resistant aggregate includes ceramsite and carbonized wear-resistant recycled coarse aggregate; the ceramsite is obtained by drying, grinding, shaping and screening, preheating and roasting, and cooling and screening the clay soil collected from the canal waste soil. The ceramsite has a continuous particle size distribution of 5 to 30 mm and an apparent density of not less than 1g / cm 3 , porosity not less than 50%, compressive strength not less than 4.5MPa, polishing value index not less than 50%; the carbonized wear-resistant recycled coarse aggregate is obtained by carbon strengthening the canal abandoned soil at a high temperature of 1000℃-1100℃ for 30-50min, the reaction product includes SiC and CaCO3, and the crushing index is not more than 13%; the recycled coarse and fine aggregate mixture is obtained by crushing, screening, grading design, mixing and curing the construction solid waste removed along the canal, and the recycled coarse and fine aggregate mixture is a continuous particle size gradation of 9.5-26.5mm; the alkali slag cementitious material is obtained by reacting slag with alkali solution; the water absorption rate of the silty clay is not less than 35%; the specific surface area of the nano diatomaceous earth is not less than 550m 2 / g, and a porosity of not less than 85%; the porosity of the outer shell protective layer is not less than 35%, and a water permeability coefficient is not less than 1cm / s.
3. The recycled cement concrete road according to claim 1, characterized in that: The recycled graded gravel is obtained by crushing, screening, shaping, cleaning and removing impurities from construction solid waste removed along the canal. The recycled graded gravel has a continuous particle size gradation of 5 to 20 mm, and the ratio of each particle size range is 5 to 10 mm: 10 to 15 mm: 15 to 20 mm = 1:1:
2. The compaction degree is not less than 97%, and the crushing index is not more than 20%.
4. The recycled cement concrete road according to claim 1, characterized in that: The fine regenerated powder is obtained by ball milling, shaping and chemical activation of waste concrete blocks from canal excavation, dismantled bridges and house buildings, and includes CaO, SiO2 and Al2O3. The MB value of the fine regenerated powder is not greater than 1.35, and the specific surface area is not less than 450m 2 / kg.
5. The recycled cement concrete road according to claim 1, characterized in that: The canal abandoned soil and slag has a moisture content of no more than 11% after refinement and dehydration; the recycled construction fine aggregate is processed from construction solid waste removed along the canal, has a particle size of no more than 4.75mm and no less than 10% of the particles pass through a 0.075mm sieve.
6. The recycled cement concrete road according to claim 1, characterized in that: The mineral composition of the high-strength cement clinker has an active mass component of not less than 90%, of which the content of tricalcium silicate is not less than 69%; the purity of the microsilica powder is greater than 86%, and the specific surface area is 16-25m 2 / g.
7. The recycled cement concrete road according to claim 1, characterized in that: The water-absorbing resin is a sodium polyacrylate resin or a cellulose-based water-absorbing resin.
8. The recycled cement concrete road according to claim 1, characterized in that: The penetration depth of the penetrating gelling material bonding layer is 1-3 cm.
9. The recycled cement concrete road according to claim 1, characterized in that: The interlayer bonding strength of the high-strength gelling bonding layer is not less than 0.8 MPa, and the compressive strength is not less than 20 MPa.
10. A construction method for a recycled cement concrete road according to any one of claims 1 to 9, characterized in that: The steps include: (1) Spoil and slag from the canal, recycled building fine aggregate and adhesive are mixed to obtain a mixture, which is laid on the base with a flatness of no more than 8 mm and a thickness of 15 cm to 20 cm, and then compacted to obtain a recycled soil base; (2) Magnesium silicate, sodium silicate, fine regeneration powder and water are uniformly stirred in a stirring device until a homogeneous bonding cementitious material is formed, and then the material is evenly spread on the regenerated soil base to form a permeable cementitious material bonding layer; (3) uniformly mixing the recycled graded crushed stone, water-absorbing resin, cement and water to form a maintenance-free recycled cement-stabilized crushed stone material, spreading, leveling and compacting the material on the permeable cementitious material bonding layer, with a compaction degree of not less than 97%, to obtain a maintenance-free recycled cement-stabilized crushed stone base layer; (4) Put high-strength cement clinker, slag powder, microsilica powder and water into a mixing equipment and mix them evenly until a homogeneous bonding cementitious material is formed. Spread the prepared cementitious material on the maintenance-free recycled cement stabilized gravel base with a spreading amount of 0.5-1kg / m 2 , obtaining a high-strength cementitious material bonding layer; (5) First, a mixture of recycled coarse and fine aggregates, water and alkali slag cementitious materials are mixed to obtain porous recycled concrete, and then the porous recycled concrete and polypropylene fiber are mixed to obtain a shell protective layer, and then silty clay, nano diatomaceous earth and the shell protective layer are mixed, and mixed evenly using a mixing device to obtain a maintenance-free material; finally, the maintenance-free material, wear-resistant aggregate, epoxy resin and water are mixed, and then evenly spread on a maintenance-free recycled cement stabilized gravel base for rolling to obtain a maintenance-free anti-skid wear layer, and the construction of the recycled cement concrete road is completed.
Citation Information
Patent Citations
Construction waste regenerated road cushion layer concrete and preparation method thereof
CN105669100A